REVITALISASI PERAN ORANG TUA DAN GURU DALAM MEMBERIKAN PENDIDIKAN SEKS PADA ANAK - Jaja Suteja; Muhsin Riyadi (IAIN Syekh Nurjati Cirebon, 2019)
Abstract: This research was conducted with a qualitative approach to the type of case studies, where data collected in the form of opinions, responses, information, concepts and information in the form of a description in expressing problems, symptoms, and phenomena in elementary schools in a careful, factual, and reasonable manner. Data collection techniques are observation, interviews, and documentation with deliberately selected informants namely elementary school class teachers, parents of students and students of SDIT. The results of this study produce that the role of parents and teachers in sex education in children includes aspects: first, teaching, namely an explanation of the male and female reproductive organs, pregnancy, ihtilam (wet dreams), menstruation and vaginal discharge. Second, Awareness that is instilling shame in children, educating children to always maintain eye contact, educating children so as not to advertise and khalwat, separating children's beds, introducing visiting times instills soul masculinity in boys and femininity in girls, choose television shows that are good for children, and also advise children to listen to music or songs that do not trigger orgasm. Third, information that explains about STIs (Sexually Transmitted Infections and HIV-Aids, as well as socialization about the types of contraceptives.Keywords: Revitalization, Role of Parents, Child Sex Education Abstrak: Penelitian ini dilaksanakan dengan pendekatan kualitatif dengan jenis studi kasus, dimana data yang dikumpulkan berupa pendapat, tanggapan, informasi, konsep-konsep dan keterangan yang berbentuk uraian dalam mengungkapkan masalah, gejala, maupun fenomena di sekolah dasar secara cermat, faktual, dan sewajarnya. Teknik pengumpulan datanya yakni dengan observasi, wawancara, dan dokumentasi dengan informan yang dipilih secara sengaja yakni guru kelas sekolah dasar, orang tua siswa dan siswa SDIT. Hasil penelitian ini menghasilkan bahwa peran orang tua dan guru dalam pendidikan seks pada anak meliputi aspek: pertama, pengajaran yakni penjelasan tentang organ reproduksi laki-laki dan perempuan, kehamilan, ihtilam (mimpi basah), haid dan keputihan. Kedua, Penyadaran yakni menanamkan rasa malu pada anak, mendidik anak agar selalu menjaga pandangan mata, mendidik anak agar tidak melakukan ikhtilat dan khalwat, memisahkan tempat tidur anak, mengenalkan waktu berkunjung menanamkan jiwa maskulinitas pada anak laki-laki dan jiwa feminitas pada anak perempuan, memilihkan tayangan televisi yang baik buat anak, dan juga menyarankan kepada anak untuk mendengarkan jenis musik atau lagu yang tidak memicu rangsangan syahwat. Ketiga, penerangan yakni menjelaskan tentang IMS (Infeksi Menular Seksual dan HIV-Aids, serta sosialisasi mengenai jenis-jenis alat kontrasepsi.Kata Kunci: Revitalisasi, Peran Orang Tua, Pendidikan Seks Anak